Brain Connectivity Predicts Chronic Pain in Acute Mild Traumatic Brain Injury. Issue 5 (9th September 2022) - Bosak, Noam; Branco, Paulo; Kuperman, Pora; Buxbaum, Chen; Cohen, Ruth Manor; Fadel, Shiri; Zubeidat, Rabab; Hadad, Rafi; Lawen, Amir; Saadon‐Grosman, Noam; Sterling, Michele; Granovsky, Yelena; et al.
Abstract : Objectives: Previous studies have established the role of the cortico‐mesolimbic and descending pain modulation systems in chronic pain prediction. Mild traumatic brain injury (mTBI) is an acute pain model where chronic pain is prevalent and complicated for prediction. In this study, we set out to study whether functional connectivity (FC) of the nucleus accumbens (NAc) and the periaqueductal gray matter (PAG) is predictive of pain chronification in early‐acute mTBI. Methods: To estimate FC, resting‐state functional magnetic resonance imaging (fMRI) of 105 participants with mTBI following a motor vehicle collision was acquired within 72 hours post‐accident. Participants were classified according to pain ratings provided at 12‐months post‐collision into chronic pain (head/neck pain ≥30/100, n = 44) and recovery (n = 61) groups, and their FC maps were compared. Results: The chronic pain group exhibited reduced negative FC between NAc and a region within the primary motor cortex corresponding with the expected representation of the area of injury. A complementary pattern was also demonstrated between PAG and the primary somatosensory cortex. PAG and NAc also shared increased FC to the rostral anterior cingulate cortex (rACC) within the recovery group. Brain connectivity further shows high classification accuracy (area under the curve [AUC] = .86) for future chronic pain, when combined with an acute pain intensity report. Interpretation: FC features obtained shortly after mTBI predict its transition to long‐term chronic pain, and may reflect an underlying interaction of injury‐related primary sensorimotor cortical areas with the mesolimbic and pain modulation systems. Our findings indicate a potential predictive biomarker and highlight targets for future early preventive interventions. ANN NEUROL 2022;92:819–833